Exposer pour exporter. Culture visuelle et expansion commerciale en Suisse (1908-1939) - Debluë, Claire-Lise (Editions Alphil Presses universitaires suisses, 2015)
In the early 20th Century, exhibitions and international fairs were a favoured field for Swiss businesses that wished to conquer new territories in foreign markets. The way in which Switzerland was represented abroad challenged traditional regional construction by substituting more geometrical lines, thereby replacing the 'chalet style'. The 'genesis' of the Swiss style of exhibition, between commercial expansion and modern architecture, is depicted here beyond that of a purely institutional history, providing a new viewpoint into its economic and artistic aspects. Particular atten-tion is given to the role of certain 'intermediaries' in the creation and diffusion of a visual culture to a commercial action.